2021
DOI: 10.3389/fphar.2021.647529
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Erchen Decoction on Gut Microbiota and Lipid Metabolism Disorders in Zucker Diabetic Fatty Rats

Abstract: Obesity is a chronic metabolic disease caused by genetic and environmental factors that has become a serious global health problem. There is evidence that gut microbiota is closely related to the occurrence and development of obesity. Erchen Decoction (ECD), a traditional Chinese medicine, has been widely used for clinical treatment and basic research of obesity and related metabolic diseases in recent years. It can significantly improve insulin resistance (IR) and lipid metabolism disorders. However, there is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 113 publications
1
35
0
Order By: Relevance
“…Moreover, our results revealed an association between Blautia genus, another bacterium of the Lachnospiraceae family, and HOMA-IR, as previously found [ 97 ]. Indeed, increased abundance of Blautia correlated with pathological manifestations such as glucose intolerance in humans [ 98 ] and IR in Zucker diabetic fatty (ZDF) rats [ 99 ] and was linked to metabolites, indicating an unfavorable metabolic state [ 100 ]. This might be related to Blautia ’s association with increased gut permeability [ 101 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, our results revealed an association between Blautia genus, another bacterium of the Lachnospiraceae family, and HOMA-IR, as previously found [ 97 ]. Indeed, increased abundance of Blautia correlated with pathological manifestations such as glucose intolerance in humans [ 98 ] and IR in Zucker diabetic fatty (ZDF) rats [ 99 ] and was linked to metabolites, indicating an unfavorable metabolic state [ 100 ]. This might be related to Blautia ’s association with increased gut permeability [ 101 ].…”
Section: Discussionmentioning
confidence: 99%
“…Erchen decoction (ECD) is a common prescription in traditional Chinese medicine (TCM) to treat obesity and its related diseases [ 12 , 13 ]. ECD is composed of Pinellia ternata, tangerine peel, Poria cocos, and Glycyrrhiza uralensis.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional Chinese medicine (TCM), which is characterized by multiple components and targets, has been widely used in clinical practice in China ( Xu et al, 2021 ; Zhao et al, 2021 ; Zhou et al, 2021 ). An increasing number of studies have indicated that TCM is playing a more important role in the treatment of chronic metabolic diseases.…”
Section: Introductionmentioning
confidence: 99%